1999
DOI: 10.1152/ajpheart.1999.277.6.h2253
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous pyruvate prolongs survival during hemorrhagic shock in swine

Abstract: Pyruvate improves cellular and organ function during hypoxia and ischemia and stabilizes the NADH redox state and cytosolic ATP phosphorylation potential. In this in vivo study, we evaluated the effects of intravenous pyruvate on cardiovascular and neocortical function, indexes of the cytosolic redox state (lactate/pyruvate ratio, L/P) and cellular energy state (adenosine and degradative products hypoxanthine and inosine, ADO + HX + Ino) during controlled arterial hemorrhage (40 mmHg) in sedated swine (45 kg).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 27 publications
7
59
1
Order By: Relevance
“…Finally, the model provides a means to explore new therapeutic strategies and pharmacology. It has been reported in animal studies that pyruvate may prolong neural survival during ischemic infarctions (48,49). Pyruvate is known to stabilize oxidative metabolism by increasing ATP production during hypoxic events.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the model provides a means to explore new therapeutic strategies and pharmacology. It has been reported in animal studies that pyruvate may prolong neural survival during ischemic infarctions (48,49). Pyruvate is known to stabilize oxidative metabolism by increasing ATP production during hypoxic events.…”
Section: Discussionmentioning
confidence: 99%
“…First, EP may function as a metabolic substrate to decrease the cytosolic NADH/NADϩ ratio and maintain the cellular phosphorylation potential ATP/ADP-Pi; this mechanism has been proposed to explain some of the beneficial effects of the parent compound pyruvate. 19 Second, EP may function as an effective scavenger of ROS, as does pyruvate. 20 Regarding this issue, we found that EP exerts a protective effect on a primary cortical culture when it is exposed to oxidative stress (Kim et al, unpublished data, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Salahudeen et al (39) reported that intravenous infusion of sodium pyruvate protects rats from renal parenchymal injury induced by injecting H 2 O 2 into the renal artery. After the publication of that paper, a number of other investigators reported that treatment with pyruvate could protect animals from the deleterious effects of a variety of conditions thought to be mediated by ROS, including myocardial I/R (4,7,8,11,35), intestinal I/R (6), and HS/R (30).…”
Section: Discussionmentioning
confidence: 99%